2013
DOI: 10.1111/jpn.12082
|View full text |Cite
|
Sign up to set email alerts
|

Changes in tissue free amino acid pools in growing chickens fed thermally treated vetch diets

Abstract: A three-day assay was developed to evaluate the effect of autoclaving on protein quality of vetch as an alternative to classical growth methods. Male chickens (n = 10/diet) were given approximately isonitrogenous diets based on raw or autoclaved vetch for 3 days. Samples of plasma, muscle and liver were obtained for free amino acid analysis. Heating vetch depressed growth (11.9 vs. 23.2 g/d; p < 0.05). Plasma methionine and histidine increased (0.05 < p < 0.06), while gluconeogenic amino acids tended to decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Free amino acid concentrations in systemic plasma illustrate the dynamic equilibrium between the post-enteral availability of amino acids and their utilisation ( Fernández-Fígares et al., 2014 ). Fundamentally, amino acids are utilised for protein accretion but are also involved in numerous metabolic and functional roles ( Wu, 2014b ).…”
Section: Discussionmentioning
confidence: 99%
“…Free amino acid concentrations in systemic plasma illustrate the dynamic equilibrium between the post-enteral availability of amino acids and their utilisation ( Fernández-Fígares et al., 2014 ). Fundamentally, amino acids are utilised for protein accretion but are also involved in numerous metabolic and functional roles ( Wu, 2014b ).…”
Section: Discussionmentioning
confidence: 99%
“…To improve the nutritive value and utilization efficiency of common vetch seeds as a feed ingredient for non‐ruminant animals, it is crucial that ANFs are inactivated or reduced in order to enable higher protein availability and effective utilization of the stored energy (Akande and Fabiyi, ). Pre‐processing methods such as selective breeding, heat treatment, soaking, chemical treatment, dehulling and germination (Lambein et al., ) not only remove or inactivate some of the ANFs in common vetch seeds, but also improve the palatability, availability and digestibility of contained nutrients (Matić et al., , ; Mikić et al., ; Akande and Fabiyi, ; Fernández‐Fígares et al., ; Oghbaeil and Prakash, ).…”
Section: Improving the Utilization Efficiency Of The Common Vetch In mentioning
confidence: 99%
“…Amino acid biosynthesis is affected by many internal factors and external environment. Previous studies have reported that different varieties, different tissues, heat treatment and nitrogen deficiency affected amino acid biosynthesis ( Hanks et al., 2003 ; Silva et al., 2004 ; El-Kereamy et al., 2012 ; Fernández-Fígares et al., 2014 ; Sun et al., 2017 ). In this experiment, we found that different rootstock grafts also affected amino acid biosynthesis in citrus peels.…”
Section: Discussionmentioning
confidence: 99%